Straightening iron material with high thermal stability and process for its production

CN122941144APending Publication Date: 2026-10-20HUIZHOU XINPENGYU NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610790197.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]然而,现有技术仍存在以下不足:(1)热变形温度与拉伸强度难以兼顾,

Benefits of technology

1、本发明在市售玻璃纤维增强的PET树脂中引入由对苯二甲酸、乙二醇、异山梨醇、四甲基环丁二醇共聚并经MDI封端改性的第二PET树脂,与第一PET树脂复合使用,利用异山梨醇和四甲基环丁二醇的刚性环状结构增强分子链刚性,提高了复合材料的拉伸强度及其高温保持率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

This invention belongs to the technical field of hair straightener materials, specifically relating to a hair straightener material with high thermal stability and its preparation process. The hair straightener material with high thermal stability comprises the following components in parts by weight: 40-60 parts of a first PET resin, 30-50 parts of a second PET resin, 0.5-0.8 parts of a heat stabilizer, 5-8 parts of an abrasion-resistant agent, 0.6-1.2 parts of a nucleating agent, and 0.2-0.3 parts of a lubricant. The hair straightener material of this invention simultaneously achieves high heat distortion temperature, high tensile strength, and high abrasion resistance, which can meet the requirements of high-end hair straighteners for long service life, high safety, and a good user experience in the clamping plate material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hair straightener material technology, specifically relating to a hair straightener material with high thermal stability and its preparation process. Background Technology

[0002] A hair straightener (commonly known as a hair straightener plate) is a hair styling tool that uses heating elements to heat and style hair. During operation, the surface temperature of the plates typically reaches over 200°C, or even higher, and must withstand repeated clamping forces and sliding friction. Therefore, the material of the hair straightener plates must possess high thermal stability to ensure that they do not deform or decompose at high temperatures, while also maintaining high strength to resist clamping and impact, and good wear resistance to prevent surface scratches and hair snagging.

[0003] Currently, hair straighteners are mainly made of thermoplastic engineering plastics, such as polyphenylene sulfide (PPS), liquid crystal polymer (LCP), and polyethylene terephthalate (PET) reinforced composites. Among them, glass fiber reinforced PET resin is used in the hair straightener field due to its good processability, electrical insulation, and high heat resistance.

[0004] However, the existing technology still has the following shortcomings: (1) It is difficult to balance heat distortion temperature and tensile strength. Increasing the heat distortion temperature of a material usually requires increasing the content of glass fiber or inorganic filler. However, excessive filler content can lead to a decrease in the interfacial bonding force between the resin matrix and the filler, exacerbating stress concentration and causing a decrease in tensile strength and brittleness of the material. (2) Insufficient wear resistance restricts service life. The straightener plate slides and rubs against the hair at high frequency during use and needs to maintain a smooth surface at high temperatures. Ordinary glass fiber reinforced PET resin has a high surface friction coefficient, and after long-term use, it is prone to wear, stringing, or surface roughening, affecting the straightening effect and user experience.

[0005] Therefore, how to achieve high heat distortion temperature, high tensile strength and high wear resistance while ensuring processing stability has become a technical problem that urgently needs to be solved in this field. It is urgent to develop a hair straightener material with high thermal stability and its preparation process to meet the requirements of high-end hair straighteners for long life, high safety and good experience of the clamping plate material. Summary of the Invention

[0006] The purpose of this invention is to provide a hair straightener material with high thermal stability and its preparation process. The hair straightener material of this invention simultaneously achieves high heat distortion temperature, high tensile strength and high wear resistance, which can meet the requirements of high-end hair straighteners for long service life, high safety and good experience of the clamping plate material.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A hair straightener material with high thermal stability comprises the following components in parts by weight: 40-60 parts of a first PET resin, 30-50 parts of a second PET resin, 0.5-0.8 parts of a heat stabilizer, 5-8 parts of an abrasion resistant agent, 0.6-1.2 parts of a nucleating agent, and 0.2-0.3 parts of a lubricant; The preparation method of the second PET resin includes the following steps: (1) Ingredients: Weigh each component according to the following mass parts: 100 parts of terephthalic acid, the molar ratio of terephthalic acid to diol is 1:(1.1-1.4), the diol includes ethylene glycol, isosorbide, and tetramethylcyclobutanediol with a molar ratio of 1:(0.4-0.5):(0.1-0.2); the catalyst is tetrabutyl titanate, the amount is 0.02-0.05 parts; the stabilizer is trimethyl phosphate, the amount is 0.01-0.03 parts; (2) Esterification reaction: Add terephthalic acid, ethylene glycol, isosorbide, tetramethylcyclobutanediol, catalyst and stabilizer from step (1) into the reaction vessel, stir and heat to 240-260℃ under nitrogen protection, the reaction pressure is 0.2-0.3MPa, the reaction time is 2.5-3.5h, and the esterification reaction is completed; (3) Pre-condensation reaction: The esterification reaction product of step (2) is fed into the polycondensation reactor, and antimony trioxide catalyst is added in an amount of 0.02-0.05 parts. The temperature is raised to 260-270℃, and the vacuum is drawn to an absolute pressure of 1000-2000Pa. The reaction time is 1-1.5h to obtain the pre-condensation product. (4) Final polycondensation reaction: Raise the temperature of the polycondensation reactor in step (3) to 275-285℃, increase the vacuum to an absolute pressure of 60Pa, and the reaction time is 2-3h to terminate the polycondensation reaction; (5) MDI end-capping treatment: After the polycondensation reaction in step (4) is completed, the melt is cooled to 240-260℃, and diphenylmethane diisocyanate is added under nitrogen protection. The amount of diphenylmethane diisocyanate added is 0.8-1.2wt% of the theoretical yield of the second PET resin. The mixture is stirred for 30-60 min to complete the end-capping. (6) Discharge and post-processing: The end-capped melt is cooled, pelletized, filtered and dried to obtain the second PET resin.

[0008] Preferably, the first PET resin is a 30-32% glass fiber reinforced flame-retardant polyethylene terephthalate resin.

[0009] Preferably, the first PET resin is DuPont™ Rynite® FR530NC010.

[0010] Most hair straighteners use single-glass fiber reinforced PET resin, such as DuPont™ Rynite® FR530NC010, a PET resin containing 30% glass fiber and flame retardant. While it has high initial tensile strength, the limited interfacial bonding between the glass fiber and the matrix, coupled with insufficient heat aging resistance of PET itself, fails to meet the long-lasting, high-strength requirements of hair straighteners. This invention introduces a second PET resin, copolymerized from terephthalic acid, ethylene glycol, isosorbide, and tetramethylcyclobutanediol and modified with MDI end-capping, into the formulation. This second resin is then used in combination with the first PET resin. The rigid cyclic structure of isosorbide and tetramethylcyclobutanediol enhances the rigidity of the molecular chains, improving the tensile strength and high-temperature retention of the composite material. Analysis shows that the introduction of rigid diols in the second PET resin restricts molecular chain movement, while MDI chain extension increases the molecular weight, synergistically enhancing matrix strength and interfacial stress transfer efficiency.

[0011] Preferably, the heat stabilizer is a complex of hindered phenolic antioxidants and phosphite antioxidants.

[0012] Preferably, the hindered phenolic antioxidant is 1098, the phosphite antioxidant is 168, and the mass ratio of the two is 1:1.

[0013] Preferably, the wear-resistant agent is polytetrafluoroethylene micro powder.

[0014] Preferably, the nucleating agent comprises sodium benzoate, polyester nanofiber nucleating agent and aluminum aromatic carboxylate in a mass ratio of (1.3-1.5):(0.8-1.0):(0.3-0.5).

[0015] In existing technologies, sodium benzoate or talc are often used alone as nucleating agents for PET, resulting in low nucleation efficiency and limited improvement in crystallization temperature, leading to poor heat distortion temperature of the material. This invention uses sodium benzoate and polyester nanofiber nucleating agent (PET) TW03) and aluminum aromatic carboxylate (BT) 20) A ternary compound was used to improve the crystallization rate and crystallinity of PET by utilizing the synergistic effect of ion cluster nucleation, nanofiber-induced nucleation, and efficient nucleation of metal carboxylate, thereby significantly increasing the heat distortion temperature. Analysis shows that the three nucleating agents provide nucleation sites at the molecular, nanoscale, and lattice scales, respectively, forming a multi-level nucleation network. This results in more complete PET crystallization and finer grains, significantly improving the material's heat distortion resistance under load. Simultaneously, the synergistic effect of sodium benzoate, polyester nanofiber nucleating agent, and aromatic aluminum carboxylate further improves the crystallization of PET molecular chains, resulting in finer grains. Higher crystallinity leads to greater surface hardness and stronger resistance to scratches and abrasion, thus improving wear resistance.

[0016] PET-TW03, a nucleating agent for polyester nanofibers, is manufactured by Tianjin Deying Technology Development Co., Ltd. PET-TW03 offers substantial improvements in the mechanical and thermal properties of polyester nanofibers. Furthermore, the polymer possesses a unique structure that allows it to penetrate the micropores of the nucleating agent.

[0017] Aromatic aluminum carboxylate, model BT-20, Tianjin Deying Technology Development Co., Ltd.

[0018] Preferably, the lubricant is calcium stearate.

[0019] The preparation process of the hair straightener material with high thermal stability includes the following steps: (1) Mix the first PET resin, the second PET resin, the heat stabilizer, the wear-resistant agent, the nucleating agent, and the lubricant evenly to obtain a mixture; (2) Add the mixture to a twin-screw extruder with a melt temperature of 275-290℃, a screw speed of 250-350rpm, a feeding speed of 10-20kg / h, a length-to-diameter ratio of 36:1-48:1, and a vacuum degree of -0.06 to -0.08MPa for extrusion granulation; (3) Injection molding: After drying the obtained granules, injection molding is performed with a barrel temperature of 275-290℃, a mold temperature of 100-120℃, and an injection pressure of ≥80MPa to obtain a hair straightener material with high thermal stability.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This invention introduces a second PET resin, which is copolymerized from terephthalic acid, ethylene glycol, isosorbide, and tetramethylcyclobutanediol and modified by MDI end-capping, into commercially available glass fiber reinforced PET resin. This second PET resin is then used in combination with the first PET resin. The rigid cyclic structure of isosorbide and tetramethylcyclobutanediol enhances the rigidity of the molecular chain, thereby improving the tensile strength and high-temperature retention rate of the composite material.

[0021] 2. This invention uses sodium benzoate and polyester nanofiber nucleating agent (PET). TW03) and aluminum aromatic carboxylate (BT) 20) By using a ternary compound, the synergistic effect of ion cluster nucleation, nanofiber-induced nucleation, and efficient nucleation of metal carboxylate salts is utilized to improve the crystallization rate and crystallinity of PET, thereby significantly increasing the heat distortion temperature. At the same time, the synergistic effect of sodium benzoate, polyester nanofiber nucleating agent, and aromatic aluminum carboxylate salt makes the PET molecular chain crystallization more complete and the grains finer. The higher the crystallinity, the greater the surface hardness of the material, and the stronger the resistance to scratches and wear, thus improving the wear resistance.

[0022] 3. The hair straightener material of the present invention simultaneously achieves high heat distortion temperature, high tensile strength and high wear resistance, which can meet the requirements of high-end hair straighteners for long service life, high safety and good experience of the plate material. Detailed Implementation

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] All raw materials used in the following embodiments of the present invention are commercially available products: PET resin, DuPont™, Rynite® FR530NC010, is a 30wt% glass fiber reinforced flame-retardant polyethylene terephthalate resin.

[0025] Polyester nanofiber nucleating agent, model PET-TW03, Tianjin Deying Technology Development Co., Ltd.

[0026] Aromatic aluminum carboxylate, model BT-20, Tianjin Deying Technology Development Co., Ltd.

[0027] Antioxidant 1098, Antioxidant 168, BASF.

[0028] Polytetrafluoroethylene (PTFE) micro powder, manufactured by Shenyang Tianyuxiang Micro Powder Materials Factory, with an average particle size D50 of 15μm.

[0029] Example 1 This embodiment provides a hair straightener material with high thermal stability, comprising the following components in parts by weight: 55 parts of a first PET resin, 40 parts of a second PET resin, 0.6 parts of a heat stabilizer, 7 parts of an abrasion resistant agent, 1.0 part of a nucleating agent, and 0.25 parts of a lubricant; the first PET resin is a 30% glass fiber reinforced flame-retardant polyethylene terephthalate resin. The first PET resin is DuPont™ Rynite® FR530NC010.

[0030] The heat stabilizer is a complex of hindered phenolic antioxidants and phosphite antioxidants. The hindered phenolic antioxidant is 1098, and the phosphite antioxidant is 168, with a mass ratio of 1:1. The wear-resistant agent is polytetrafluoroethylene micropowder. The nucleating agent comprises sodium benzoate, polyester nanofiber nucleating agent, and aluminum aromatic carboxylate in a mass ratio of 1.4:0.9:0.4. The lubricant is calcium stearate.

[0031] The preparation method of the second PET resin includes the following steps: (1) Ingredients: Weigh each component according to the following mass parts: 100 parts of terephthalic acid, the molar ratio of terephthalic acid to diol is 1:1.3, the diol includes ethylene glycol, isosorbide, and tetramethylcyclobutanediol with a molar ratio of 1:0.4:0.2; the catalyst is tetrabutyl titanate, the amount is 0.04 parts; the stabilizer is trimethyl phosphate, the amount is 0.02 parts; (2) Esterification reaction: Terephthalic acid, ethylene glycol, isosorbide, tetramethylcyclobutanediol, catalyst and stabilizer from step (1) are added to the reaction vessel, stirred and heated to 250°C under nitrogen protection, the reaction pressure is 0.3 MPa, the reaction time is 3 h, and the esterification reaction is completed. (3) Pre-condensation reaction: The esterification reaction product of step (2) is fed into the polycondensation reactor, and antimony trioxide catalyst is added in an amount of 0.03 parts. The temperature is raised to 265°C, and the vacuum is drawn to an absolute pressure of 2000 Pa. The reaction time is 1.2 h to obtain the pre-condensation product. (4) Final polycondensation reaction: raise the temperature of the polycondensation reactor in step (3) to 280°C, increase the vacuum to an absolute pressure of 60Pa, and the reaction time is 2.5h to terminate the polycondensation reaction; (5) MDI end-capping treatment: After the polycondensation reaction in step (4) is completed, the melt is cooled to 250°C, and diphenylmethane diisocyanate is added under nitrogen protection. The amount of diphenylmethane diisocyanate added is 1.0 wt% of the theoretical yield of the second PET resin. The mixture is stirred for 50 min to complete the end-capping. (6) Discharge and post-processing: The end-capped melt is cooled, pelletized, filtered and dried to obtain the second PET resin.

[0032] The preparation process of the hair straightener material with high thermal stability includes the following steps: (1) Mix the first PET resin, the second PET resin, the heat stabilizer, the wear-resistant agent, the nucleating agent, and the lubricant evenly to obtain a mixture; (2) Add the mixture to the twin-screw extruder. The melting temperature is 280℃, the screw speed is 300rpm, the feeding speed is 15kg / h, the length-to-diameter ratio of the twin-screw extruder is 40:1, the vacuum degree is -0.06MPa, and the extrusion granulation is performed. The temperature settings of each zone of the twin-screw extruder are as follows: Zone 1 230℃, Zone 2 250℃, Zone 3 265℃, Zone 4 275℃, Zone 5 285℃, Zone 6 285℃, Zone 7 280℃, Zone 8 275℃, Zone 9 270℃, and the die head temperature is 280℃.

[0033] (3) Injection molding: After drying the obtained granules, injection molding is performed with a barrel temperature of 280℃, a mold temperature of 120℃, and an injection pressure of 80MPa to obtain a hair straightener material with high thermal stability.

[0034] Example 2 This embodiment provides a hair straightener material with high thermal stability, comprising the following components in parts by weight: 60 parts of a first PET resin, 40 parts of a second PET resin, 0.8 parts of a heat stabilizer, 5 parts of an abrasion resistant agent, 1.2 parts of a nucleating agent, and 0.2 parts of a lubricant; the first PET resin is a 30% glass fiber reinforced flame-retardant polyethylene terephthalate resin. The first PET resin is DuPont™ Rynite® FR530NC010.

[0035] The heat stabilizer is a complex of hindered phenolic antioxidants and phosphite antioxidants. The hindered phenolic antioxidant is 1098, and the phosphite antioxidant is 168, with a mass ratio of 1:1. The wear-resistant agent is polytetrafluoroethylene micropowder. The nucleating agent comprises sodium benzoate, polyester nanofiber nucleating agent, and aluminum aromatic carboxylate in a mass ratio of 1.3:1.0:0.3. The lubricant is calcium stearate.

[0036] The preparation method of the second PET resin includes the following steps: (1) Ingredients: Weigh each component according to the following mass parts: 100 parts of terephthalic acid, the molar ratio of terephthalic acid to diol is 1:1.3, the diol includes ethylene glycol, isosorbide, and tetramethylcyclobutanediol with a molar ratio of 1:0.4:0.2; the catalyst is tetrabutyl titanate, the amount is 0.04 parts; the stabilizer is trimethyl phosphate, the amount is 0.02 parts; (2) Esterification reaction: Terephthalic acid, ethylene glycol, isosorbide, tetramethylcyclobutanediol, catalyst and stabilizer from step (1) are added to the reaction vessel, stirred and heated to 250°C under nitrogen protection, the reaction pressure is 0.3 MPa, the reaction time is 3 h, and the esterification reaction is completed. (3) Pre-condensation reaction: The esterification reaction product of step (2) is fed into the polycondensation reactor, and antimony trioxide catalyst is added in an amount of 0.03 parts. The temperature is raised to 265°C, and the vacuum is drawn to an absolute pressure of 2000 Pa. The reaction time is 1.2 h to obtain the pre-condensation product. (4) Final polycondensation reaction: raise the temperature of the polycondensation reactor in step (3) to 280°C, increase the vacuum to an absolute pressure of 60Pa, and the reaction time is 2.5h to terminate the polycondensation reaction; (5) MDI end-capping treatment: After the polycondensation reaction in step (4) is completed, the melt is cooled to 250°C, and diphenylmethane diisocyanate is added under nitrogen protection. The amount of diphenylmethane diisocyanate added is 1.0 wt% of the theoretical yield of the second PET resin. The mixture is stirred for 50 min to complete the end-capping. (6) Discharge and post-processing: The end-capped melt is cooled, pelletized, filtered and dried to obtain the second PET resin.

[0037] The preparation process of the hair straightener material with high thermal stability includes the following steps: (1) Mix the first PET resin, the second PET resin, the heat stabilizer, the wear-resistant agent, the nucleating agent, and the lubricant evenly to obtain a mixture; (2) Add the mixture to the twin-screw extruder. The melting temperature is 280℃, the screw speed is 300rpm, the feeding speed is 15kg / h, the length-to-diameter ratio of the twin-screw extruder is 40:1, the vacuum degree is -0.06MPa, and the extrusion granulation is performed. The temperature settings of each zone of the twin-screw extruder are as follows: Zone 1 230℃, Zone 2 250℃, Zone 3 265℃, Zone 4 275℃, Zone 5 285℃, Zone 6 285℃, Zone 7 280℃, Zone 8 275℃, Zone 9 270℃, and the die head temperature is 280℃. (3) Injection molding: After drying the obtained granules, injection molding is performed with a barrel temperature of 280℃, a mold temperature of 120℃, and an injection pressure of 80MPa to obtain a hair straightener material with high thermal stability.

[0038] Comparative Example 1 The difference between this comparative example and Example 1 is that the diol includes ethylene glycol and isosorbide in a molar ratio of 1:0.4.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that the diol includes ethylene glycol and tetramethylcyclobutanediol in a molar ratio of 1:0.2. Comparative Example 3 The difference between this comparative example and Example 1 is that the diol includes ethylene glycol, isosorbide, and tetramethylcyclobutanediol in a molar ratio of 1:0.2:0.4.

[0040] Comparative Example 4 The difference between this comparative example and Example 1 is that the nucleating agent includes sodium benzoate and aluminum aromatic carboxylate in a mass ratio of 1.4:0.4.

[0041] Comparative Example 5 The difference between this comparative example and Example 1 is that the nucleating agent includes sodium benzoate and polyester nanofiber nucleating agent in a mass ratio of 1.4:0.9.

[0042] Comparative Example 6 The difference between this comparative example and Example 1 is that the nucleating agent includes sodium benzoate, polyester nanofiber nucleating agent and aluminum aromatic carboxylate in a mass ratio of 1:1:1.

[0043] Performance testing The performance of the hair straightener materials prepared in Examples 1-2 and Comparative Examples 1-6 was tested.

[0044] 1. Heat distortion temperature: "Determination of heat distortion temperature of plastics - Part 2: Plastics and hard rubber" (GB / T1634.2-2019) 2. Tensile strength: "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics" (GB / T1040.2-2022).

[0045] 3. Wear resistance: Samples measuring 3cm × 2cm × 0.5cm were prepared and their wear resistance was tested using a multi-functional friction and wear testing machine; the counter sample was steel 440. C, the rotational speed is 400 r / min, the load is 100 N, the test time is 1 h, and the wear amount is measured by weighing method.

[0046] The performance test results are shown in Table 1.

[0047] Table 1 Performance Test Results

[0048] As shown in Table 1, the hair straightener materials prepared in Examples 1-2 of this invention exhibit excellent heat distortion temperature, tensile strength, and abrasion resistance. This invention introduces a second PET resin, copolymerized from terephthalic acid, ethylene glycol, isosorbide, and tetramethylcyclobutanediol and modified with MDI end-capping, into commercially available glass fiber reinforced PET resin. In the second PET resin, isosorbide and tetramethylcyclobutanediol are both rigid diols; their rigid cyclic structure effectively restricts the free movement of molecular chains, improving the regularity and crystallinity of the molecular chains. The MDI end-capping treatment further increases the molecular weight and seals the terminal carboxyl groups, enhancing the matrix strength and interfacial stress transfer efficiency. When the two PET resins are used in combination, the rigid segments of the second PET resin and the glass fiber skeleton of the first PET resin form an interpenetrating network, synergistically improving the tensile strength and its high-temperature retention rate. Simultaneously, the introduction of rigid segments enhances the material's creep resistance under load, giving the material a higher heat distortion temperature. This invention employs a ternary compound of sodium benzoate, polyester nanofiber nucleating agent, and aluminum aromatic carboxylate. The three nucleating agents provide nucleation sites at the molecular, nanoscale, and lattice scales, respectively, forming a multi-level nucleation network that results in more complete PET crystallization and finer, more uniform grains. Increased crystallinity directly enhances the material's resistance to heat deformation under load, i.e., a significantly higher heat distortion temperature. Simultaneously, more complete crystallization and finer grains lead to greater surface hardness and stronger resistance to scratches and abrasion, thus improving wear resistance. Furthermore, the highly complete crystalline structure reduces defects in amorphous regions, facilitating uniform stress transmission and positively impacting tensile strength.

[0049] In Comparative Example 1, the second PET resin used only ethylene glycol and isosorbide, lacking tetramethylcyclobutanediol. Tetramethylcyclobutanediol has higher cyclic structure rigidity and thermal stability. Its absence leads to insufficient rigidity of the second PET resin molecular chain, reduced crystallization ability, and thus lower heat distortion temperature, lower tensile strength, and increased wear.

[0050] In Comparative Example 2, the second PET resin used only ethylene glycol and tetramethylcyclobutanediol as diols, lacking isosorbide. The rigid bicyclic structure of isosorbide contributes more to the rigidity of the molecular chain than tetramethylcyclobutanediol. Its absence increases the flexibility of the molecular chain, making the material more prone to deformation under load. At the same time, the interfacial stress transfer efficiency is reduced, resulting in lower heat distortion temperature and tensile strength than in the example, and a correspondingly worse wear resistance.

[0051] In Comparative Example 3, the diol ratio of the second PET resin was adjusted to a molar ratio of ethylene glycol, isosorbide, and tetramethylcyclobutanediol of 1:0.2:0.4. The rigid bicyclic structure of isosorbide is more efficient in improving the rigidity of the molecular chain, and the overall rigidity decreases when the content is insufficient. At the same time, the imbalance in the ratio of the two rigid diols destroys the optimal synergistic effect.

[0052] Comparative Example 4 used only sodium benzoate and aluminum aromatic carboxylate as nucleating agents, lacking the polyester nanofiber nucleating agent. The nanofiber network structure provided by the polyester nanofiber nucleating agent can induce the formation of a large number of crystal nuclei at the nanoscale. The absence of the nucleating agent significantly reduces the number of nucleation sites, decreases the crystallization rate, and results in incomplete crystallization, leading to a significant decrease in heat distortion temperature and wear resistance.

[0053] Comparative Example 5 used only sodium benzoate and polyester nanofiber nucleating agents, lacking aluminum aromatic carboxylate. Aluminum aromatic carboxylate provides efficient nucleation at the lattice scale; its absence reduces overall nucleation efficiency, limits the increase in crystallization temperature, and results in insufficient crystallinity, leading to a decrease in heat distortion temperature, increased wear, and reduced tensile strength.

[0054] In Comparative Example 6, the nucleating agent was a mixture of sodium benzoate, polyester nanofiber nucleating agent, and aluminum aromatic carboxylate in a 1:1:1 mass ratio. This imbalance prevented the synergistic effect of the three nucleating agents from being fully realized: a higher proportion of sodium benzoate could lead to excessive local concentrations causing nucleation site aggregation; a higher proportion of polyester nanofiber nucleating agent might cause fiber agglomeration; and a higher proportion of aluminum aromatic carboxylate might act as an impurity, interfering with crystallization. Therefore, the material's heat distortion temperature, tensile strength, and abrasion resistance were all inferior to those of Example 1.

[0055] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A hair straightener material with high thermal stability, characterized in that, It includes the following components in parts by weight: 40-60 parts of first PET resin, 30-50 parts of second PET resin, 0.5-0.8 parts of heat stabilizer, 5-8 parts of wear-resistant agent, 0.6-1.2 parts of nucleating agent, and 0.2-0.3 parts of lubricant.

2. The hair straightener material with high thermal stability according to claim 1, characterized in that, The preparation method of the second PET resin includes the following steps: (1) Ingredients: Weigh each component according to the following mass parts: 100 parts of terephthalic acid, the molar ratio of terephthalic acid to diol is 1:(1.1-1.4); the catalyst is tetrabutyl titanate, the amount is 0.02-0.05 parts; the stabilizer is trimethyl phosphate, the amount is 0.01-0.03 parts; (2) Esterification reaction: Add the terephthalic acid, diol, catalyst and stabilizer from step (1) into the reaction vessel, stir and heat to 240-260℃ under nitrogen protection, the reaction pressure is 0.2-0.3MPa, the reaction time is 2.5-3.5h, and the esterification reaction ends. (3) Pre-condensation reaction: The esterification reaction product of step (2) is fed into the polycondensation reactor, and antimony trioxide catalyst is added in an amount of 0.02-0.05 parts. The temperature is raised to 260-270℃, and the vacuum is drawn to an absolute pressure of 1000-2000Pa. The reaction time is 1-1.5h to obtain the pre-condensation product. (4) Final polycondensation reaction: Raise the temperature of the polycondensation reactor in step (3) to 275-285℃, increase the vacuum to an absolute pressure of 60Pa, and the reaction time is 2-3h to terminate the polycondensation reaction; (5) MDI end-capping treatment: After the polycondensation reaction in step (4) is completed, the melt is cooled to 240-260℃, and diphenylmethane diisocyanate is added under nitrogen protection. The amount of diphenylmethane diisocyanate added is 0.8-1.2wt% of the theoretical yield of the second PET resin. The mixture is stirred for 30-60 min to complete the end-capping. (6) Discharge and post-processing: The end-capped melt is cooled, pelletized, filtered and dried to obtain the second PET resin.

3. The hair straightener material with high thermal stability according to claim 2, characterized in that, The diols include ethylene glycol, isosorbide, and tetramethylcyclobutanediol in a molar ratio of 1:(0.4-0.5):(0.1-0.2).

4. The hair straightener material with high thermal stability according to claim 1, characterized in that, The first PET resin is a polyethylene terephthalate resin reinforced with 30-32 wt% glass fiber.

5. The hair straightener material with high thermal stability according to claim 1, characterized in that, The heat stabilizer is a complex of hindered phenolic antioxidants and phosphite antioxidants.

6. The hair straightener material with high thermal stability according to claim 5, characterized in that, The hindered phenolic antioxidant is antioxidant 1098, and the phosphite antioxidant is antioxidant 168.

7. The hair straightener material with high thermal stability according to claim 1, characterized in that, The wear-resistant agent is polytetrafluoroethylene micro powder.

8. The hair straightener material with high thermal stability according to claim 1, characterized in that, The nucleating agent comprises sodium benzoate, polyester nanofiber nucleating agent, and aluminum aromatic carboxylate in a mass ratio of (1.3-1.5):(0.8-1.0):(0.3-0.5).

9. The hair straightener material with high thermal stability according to claim 1, characterized in that, The lubricant is calcium stearate.

10. A process for preparing a hair straightener material with high thermal stability according to any one of claims 1-9, characterized in that, Includes the following steps: (1) Mix the first PET resin, the second PET resin, the heat stabilizer, the wear-resistant agent, the nucleating agent, and the lubricant evenly to obtain a mixture; (2) Add the mixture to a twin-screw extruder with a melt temperature of 275-290℃, a screw speed of 250-350rpm, a feeding speed of 10-20kg / h, a length-to-diameter ratio of 36:1-48:1, and a vacuum degree of -0.06 to -0.08MPa for extrusion granulation; (3) Injection molding: After drying the obtained granules, injection molding is performed with a barrel temperature of 275-290℃, a mold temperature of 100-120℃, and an injection pressure of ≥80MPa to obtain a hair straightener material with high thermal stability.